Intestinal Helminth Infections and Risk Factors in Companion Cats of Dhaka, Bangladesh - Mukutmoni, Mandira; Musa, Sharmin; Khanum, Hamida (Bangladesh Journal of Zoology, 2022)
The present study was intended to determine the prevalence and associated risk factors for parasitic infection in companion cats from Dhaka, Bangladesh. A total of 216 fecal samples of companion cats from Dhaka city were collected. A questionnaire survey was conducted among the cat owners to collect various data on the companion cats viz. age, breed, food, clinical issues, behavior etc. Double centrifugal flotation technique was used to process the fecal samples. In total 70 fecal samples of cat were found to be infected with at least one helminth parasite. Hookworms showed the highest prevalence (9.26%) followed by Trichuris vulpis (7.41%), Dipylidium spp. (6.02%) and Toxocara cati (4.63%). Parasitic infections were prevalent among the cats aged one to two years old (71.43%). Local breed cats were more prone to parasitic infections (67.14%). Outdoor access (70%), irregular deworming (50%) and providing homemade food (70%) were significantly associated with high prevalence of parasitic infections (P < 0.05). The maximum helminth positive cats were found to have irregular bowel movement or constipation (22.86%) and sneezing (22.86%) (P=0.000). The maximum helminth infected cats showed aggression towards other animals (34.28%). Behaviors such as scratching furniture’s (17.14%) and excessive vocalization (15.71%) were also common among the infected cats. A total of 182 (84.26%) cat owners had idea about zoonosis whereas 34 (15.74%) were unaware of it. The owners who knew about zoonosis, their cats were mostly free of infection (93.15%). Pet owners’ alertness towards cats’ behavior, clinical symptoms, prophylactic measures and overall hygiene management may be operative to lower the possibility of zoonotic transmission of parasites. Bangladesh J. Zool. 50 (1): 95-105, 2022